Comparative analysis between challenges in a Brazilian perspective and worldwide initiatives in Advanced Manufacturing - Mancilha, Guilherme; Gomes, Jefferson (Brazilian Journal of Operations & Production Management, 2018)
The purpose of this paper is to analyze possible actions to overcome the challenges in the process of development Advanced Manufacturing in Brazil, based on a comparative analysis of projects developed in these subjects in other countries and a survey of research intensity on the theme. The first step is the survey of Brazil’s Challenges in Advanced Manufacturing based on the results of a series of workshops conducted by the Brazilian government with experts, followed by validation and consolidation of results by confronting with a National Confederation of Industries’ survey on Industry 4.0. The second brings a survey of the intensity and relevance of the research on the main aspects of the theme. The last step presents a correlation of the main challenges raised in the first step with global initiatives that work on these subjects, as well as a detailed analysis of the main challenges. The results highlight a direction for the sector from the analysis of research intensity on the themes and a matrix with 40 initiatives correlated to this challenge. From that, it is possible to conclude that the challenges can be overcome by integrating government, companies and universities into initiatives focused on the technologies needed to serve the priority sectors.